Fluid-Structure Interaction Simulation of Heart Valve Flows by a Hybrid Immersed-Boundary/Body-Fitted-Grid Method (Advances in Applied Mathematics and Mechanics, 2025)
In this paper, a hybrid Immersed-Boundary/Body-Fitted-Grid method isextended to simulate the complex fluid-structure-interaction (FSI) problems involvedin the flows through a bileaflet mechanical heart valve (BMHV). The background gridis discretized with a body-fitted gird while the freely-rotating leaflets are treated byan immersed boundary method named the local domain-free-discretization (DFD)method. For simulation of turbulence involved in BMHV flows, the wall-modelledlarge eddy simulation is implemented in the DFD framework. In order to address theinstability issue associated with low-mass structures, the strong coupling (SC) strategy is employed. To accelerate the convergence of SC-FSI sub-iteration, we adopt theunder-relaxion scheme with an optimal relaxion coefficient and Hamming’s 4th-orderpredictor-corrector scheme. To validate the SC schemes for low-mass structures, numerical experiments on the vortex induced vibration of an elastically mounted cylinder are carried out. Finally, the present method is applied to simulate and investigate the pulsatile flows through a BMHV at physiologic conditions, in which complexfluid-structure interactions are involved. The computed results agree well with thepublished numerical or experimental data.